2010
DOI: 10.1016/j.ceb.2010.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Germline stem cells: stems of the next generation

Abstract: Germline stem cells (GSCs) sustain gametogenesis during the life of organisms. Recent progress has substantially extended our understanding of GSC behavior, including the mechanisms of stem cell self-renewal, asymmetric stem cell division, stem cell niches, dedifferentiation, and tissue aging. GSCs typically are highly proliferative, due to organismal requirement to produce large number of differentiated cells. While many somatic stem cells are multipotent, with potentially multiple differentiation pathways, G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 70 publications
0
17
0
Order By: Relevance
“…C) by the SV cells; “light blue outlined by gray” in Fig. C), and (c) its location at the terminal end of the tubular structure in the testis . Moreover, this study shows that some of SV cells are still capable of proliferation in the adult stage and then appear to contribute to the Sertoli cells within the convoluted seminiferous epithelia (Fig.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…C) by the SV cells; “light blue outlined by gray” in Fig. C), and (c) its location at the terminal end of the tubular structure in the testis . Moreover, this study shows that some of SV cells are still capable of proliferation in the adult stage and then appear to contribute to the Sertoli cells within the convoluted seminiferous epithelia (Fig.…”
Section: Discussionmentioning
confidence: 60%
“…Much of our understanding regarding the mechanism of maintenance of the germline stem cells is derived from the gonads of two invertebrate organisms, Drosophila melanogaster and Caenorhabditis elegans . Although the testicular architecture is different in these species, the germline stem cells are housed similarly in a defined niche environment, which is restricted to the terminal segment of the tubular structure populated by specialized somatic cell structures such as “hub cells” in Drosophila and “distal tip cells” in C. elegans . It has been shown that in this tubular end, specialized somatic cells provide the necessary cues for stem cell maintenance to the closest germ line stem cells in addition to repressing their differentiation via short‐ and long‐range signaling factors, including TGFβ‐like signaling molecules .…”
Section: Introductionmentioning
confidence: 99%
“…Besides identification of signals and mechanisms involved in stem cell maintenance and differentiation, these studies have also revealed mechanisms underlying stem cell and niche interaction, essential for maintenance of healthy stem cell populations (Losick et al, 2011; Pearson et al, 2009; Hsu et al, 2014; Gunage et al, 2014; Yuan and Yamashita, 2010; Lin, 2002; Singh et al, 2007; Inaba et al, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…Multipotent stem cells have the ability to self renew and develop into multiple tissues or differentiated cell types, such as hematopoietic progenitor cells that develop into different types of blood cells (Seita and Weissman, 2010;Wright, 1981). Unipotent stem cells have the ability to self renew and develop into one tissue type or differentiated cell type, such as the germline stem cells in the adult gonad (Brown and Swalla, 2007;Yuan and Yamashita, 2010). Fig.…”
Section: Evolutionary Cell Lineage Modification Modelsmentioning
confidence: 99%